Pengaruh Kinerja Aset Terhadap Kepuasan Pengguna Terminal Pasir Hayam Cianjur (Studi Kasus Menurut Persepsi Pengguna) - Isti Wulandari; Tri Setyowati; Nurlaila Fadjarwati (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Pasir Hayam Terminal is a passenger terminal that functions as the main land transportation center in Cianjur Regency. Despite its strategic role, the terminal still encounters several asset performance issues, including unclear departure and arrival lanes, limited seating in the waiting area, inadequate lighting, damaged access roads, and the absence of ticket counters. This study aims to analyze the influence of asset performance on user satisfaction at Pasir Hayam Terminal. Asset performance is assessed using four dimensions: Safety and Security, Access, Information, and Allied Facilities. User satisfaction is measured through expectation conformity, intention to revisit, and willingness to recommend. A mixed-method approach is applied in this study. Quantitative data were collected using questionnaires and analyzed through IBM SPSS Statistics 26, employing tests such as validity, reliability, normality, simple linear regression, and t-tests. Qualitative data were obtained through observation and interviews, then analyzed through data reduction, data display, and conclusion drawing. The results indicate that asset performance is in the “moderate” category with a mean score of 3.089, although improvements are needed in information availability and accessibility. User satisfaction is also considered moderate, with a mean score of 2.738. While users perceive the facilities as generally meeting expectations, their willingness to recommend the terminal remains low. Regression analysis reveals that asset performance significantly influence user satisfaction, with an R² value of 0.557 it means 55.7% of satisfaction is influenced by asset performance. These findings suggest that enhancing asset performance could substantially improve user satisfaction at Pasir Hayam Terminal.